Electrochemical oxidation of butein at glassy carbon electrodes - Tesio, Alvaro Yamil (2013)
The electrochemical oxidation of flavonoid butein is studied at glassy carbon electrodes in phosphate and citrate buffer solutions of different pH values, and 1M perchloric acid aqueous solutions by cyclic and square wave voltammetries. The oxidation peak corresponds to the 2e, 2H oxidation of the 3,4-dihydroxy group in B ring of butein, given the corresponding quinone species. The overall electrode process shows a quasi-reversible behavior and an adsorption/diffusion mixed control at high butein bulk concentrations. At low butein concentrations, the electrode process shows mainly an adsorption control. Butein surface concentration values were obtained from the charge associated with the adsorbed butein oxidation peaks, which are in agreement with those values expected for the formation of a monolayer of adsorbate in the concentration range from 1 to 5μM. Square wave voltammetry was used to perform a full thermodynamic and kinetics characterization of the butein surface redox couple. Therefore, from the combination of the "quasi-reversible maximum" and the "splitting of the net square wave voltammetric peak" methods, values of (0.386±0.003) V, (0.46±0.04), and 2.7×10s were calculated for the formal potential, the anodic transfer coefficient, and the formal rate constant, respectively, of the butein overall surface redox process in pH4.00 citrate buffer solutions. These results will be then used to study the interaction of butein, and other flavonoids with the deoxyribonucleic acid, in order to better understand the potential therapeutic applications of these compounds.